Potential Hazards Associated with the Consumption of Crustaceans: The Egyptian Scenario - Abd El-Salam E. Hafez; Rasha M. Elbayomi; Sara M. El Nahal; Ahmed E. Tharwat; Darwish, Wageh (Journal of Advanced Veterinary Research, 2022)
Crustaceans such as shrimp and crab are considered as a rich source of protein, omega 3 fatty acids and trace elements. However, they are exposed to a vast array of xenobiotics during their lifetime such as heavy metals, pesticides, and dioxins. Moreover, crustaceans are also implicated in the transmission of many foodborne pathogens such as Aeromonas hydrophila, Staphylococcus aureus, Vibrio parahemolyticus, and others. They are also rich in biogenic amines such as histamine and cadaverine, and they might cause severe allergic reactions in highly susceptible people. This review summarized the current scenario of potential hazards associated with the consumption of crustaceans in Egypt.